A rare presentation of Sacrococcygeal Teratoma as recurrent natal cleft abscess in childhood - Daniel Pasquale Cinelli; Ionica Stoica; Fadi Atwan; Sri Paran (Elsevier, 2021)
We report the case of a seven year old girl presenting with recurrent left natal cleft abscess who was diagnosed with Sacrococcygeal Teratoma (SCT) after having multiple Incision and Drainages (I&Ds). Diagnosis was made with intraoperative digital rectal examination (DRE) and MRI Pelvis. Complete surgical resection was performed and histopathology identified mature SCT with clear margins throughout the entire specimen. At nine month follow-up, she remained well with no evidence of recurrence. To the author's knowledge, this is the first case report of SCT presenting as recurrent natal cleft abscess in a child.